The influence of grooming style on recruiters' evaluations of female applicants for a managerial position : a thesis presented in partial fulfilment of the requirements of Master of Business Studies in Communication Management, at Massey University, Palmerston North - Heke, Joanna (Massey University, 2010)
In an ideal world, employment assessments would only be based on rational decision-making involving, for example, the evaluation of employment history, education, references and demonstrable experience (Kyle & Mahler, 1996). However, physical appearance plays a significant role in interpersonal communications because it functions as a readily available source of nonverbal information (Graham & Jouhar, 1980). The aim of this research project was to examine how employment decisions regarding women in management might be influenced by gender-related aspects of women’s grooming style. Evaluations from 114 British recruitment consultants were used to determine the influence of cosmetics, hairstyle and eyeglasses on impressions and evaluations of a female managerial job applicant. Eight variations of cosmetics, hairstyle and eyeglasses were used in the experimental treatments. Recruitment consultants viewed an identical job description and Curriculum Vitae for the fictional job applicant with one of the eight head and shoulders colour photos attached, and rated the job applicant on a number of impressions related to personal qualities and employment potential. The data gained were analysed using analysis of variance. Results indicated that amendments to the grooming conditions did not significantly affect perceptions of employment potential, competence, independence or recommendations of salary. However, there were some significant main effects of femininity and masculinity related to the job applicant’s hairstyle and the respondents’ gender. Hairstyle changes had the strongest impact on the model’s perceived femininity and masculinity, with long hair significantly enhancing perceived femininity. Interestingly, female respondents gave significantly higher masculinity ratings to the job applicant than did male iii respondents. There were also a number of other significant two-way interactions that serve to consolidate the main grooming interactions found regarding femininity and masculinity. The two-way interaction between hairstyle and eyeglasses was significant for the reactions concerning ‘employment potential’, ‘would work well under direction’ and ‘practical’, and came near significance for the participants’ impressions of ‘competence’. In responding to all of these differently presented views of the same person, under the impressions listed above, it appears that respondents gave higher scores when they viewed the job applicant with a balance of grooming elements that were masculine (hair up, eyeglasses and no cosmetics) and feminine (hair down, no eyeglasses and cosmetics). Therefore, a job applicant with a very feminine appearance is perhaps not seen as appropriate for a managerial role compared with a moderately feminine-seeming applicant and likewise, a very masculine appearance may also be considered a less likely indicator of future success in a managerial role.
Keywords: Female job applicants; Personal appearance; Grooming style; Recruiters' evaluations; Communication management; Business studies